An Unruly Classic, Kalīla and Dimna and Its Syriac, Arabic, and Early Persian Versions - Isabel Toral; Beatrice Gruendler (Brill, 2024)
In this collected volume, members of the Kalīla and Dimna project discuss, from different perspectives, a core aspect of their work with this textual tradition: the study of variation and mutability. The aim is to shed light on Kalīla and Dimna's so-called mouvance and establish typologies of textual mobility and instability across linguistic traditions and historical periods, as well as to develop analytical tools to describe, classify, represent, and interpret these dynamics. As will be shown, the progressive digitalization of philology in the last decades has offered the unique opportunity of putting the concept of mouvance into practice. Contributors: Theodore S. Beers, Jan J. van Ginkel, Beatrice Gründler, Khouloud Khalfallah, Mahmoud Kozae, Rima Redwan, Johannes Stephan, Isabel Toral.